Evaluation of MPA designs that protect highly mobile megafauna now and under climate change scenarios - M.E. Gilmour (Global Ecology and Conservation, 2022)
Marine protected area (MPA) designs, including large-scale MPAs (LSMPAs; >150,000 km2), mobile MPAs (fluid spatiotemporal boundaries), and MPA networks, may offer different benefits to species and could enhance protection by encompassing spatiotemporal scales of animal movement. We sought to understand how well LSMPAs could benefit nine highly-mobile marine species in the tropics now and into the future by: 1) evaluating current range overlap within a LSMPA; 2) evaluating range overlap under climate change projections; and 3) evaluating how well theoretical MPA designs benefit these nine species. We focused on Palmyra Atoll and Kingman Reef, a 2000 km2 area within the 1.2 million km2 U.S. Pacific Remote Islands Marine National Monument (PRIMNM) that contains marine megafauna (reef and pelagic fishes; sea turtles; seabirds; cetaceans) reflecting different behaviors and habitat use. Our approach is useful for evaluating the effectiveness of the Palmyra-Kingman MPA and PRIMNM in protecting these species, and tropical LSMPAs in general, and for informing future MPA design. Stationary MPAs provided protection at varying scales. Reef manta rays (Mobula alfredi), grey reef sharks (Carcharhinus amblyrhynchos), green sea turtles (Chelonia mydas), and bottlenose dolphins (Tursiops truncatus) had overall small ranges (<100 km from Palmyra-Kingman) and could benefit from stationary MPAs that contained heterogenous reef habitats. Yellowfin tuna (Thunnus albacares), sooty terns (Onychoprion fuscatus), red-footed boobies (Sula sula), great frigatebirds (Fregata minor), and melon-headed whales (Peponocephala electra) navigated complex oceanographic processes and may benefit most from mobile MPAs that shift with features including thermal fronts, cyclic regions of elevated productivity, and eddies, if relationships with these features are established and predictable. All species had capacity to travel to nearby reef systems, illustrating potential benefits of MPA networks and protected corridors. Suitable habitats will likely contract for all species as warm water expands under climate change scenarios (species habitats were predicted to decrease by 4–49% at Palmyra-Kingman) and MPAs may not protect suitable habitats into the future. Species habitat requirements and movement ecologies are critical aspects of marine spatial planning, especially with respect to dynamic ocean processes and a changing climate.